Exploring the need and potential of ambulatory pharmacy practice for empowering patient and care delivery in India - Choudhary, Ravindra P.; Siddalingegowda, Srikanth M. (Frontiers in Health Services, 2024)
In recent years, rapidly changing disease profile patterns, shortage & uneven utilization of healthcare professionals contributed massive burden on the Indian healthcare system, which resulted in varying, fragmented, inconsistent healthcare delivery to the patients and poor patient management. Patients often face and experience many challenges like lack of accessibility, poor patient–healthcare provider relationships, and inadequate quality of care, resulting in unnecessary economic burden in managing their health conditions. Thus Indian healthcare reform is essential in enhancing its capacity to fulfill patients' health needs that can be addressed by focusing on key sustainable strategies and initiatives meant for enhancing coordination of care, expanding services accessibility, redeveloping healthcare infrastructure, implementing workforce innovation and strong governance with the incorporation of core principles such as patient-centeredness, integrated care and collaborative care approaches. The clinical and ambulatory pharmacy practice are fragment of the healthcare delivery which delivers pharmaceutical care and fulfils the needs of patients across healthcare settings. This paper focuses on the present & future perspectives of ambulatory pharmacy practice in India and the factors to be considered for implementing it in patient care.